2013
DOI: 10.1371/journal.pone.0056215
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Albuminuria and Hypertension and Arrest of Severe Renal Injury by a Losartan-Hydrochlorothiazide Association in a Model of Very Advanced Nephropathy

Abstract: Treatments that effectively prevent chronic kidney disease (CKD) when initiated early often yield disappointing results when started at more advanced phases. We examined the long-term evolution of renal injury in the 5/6 nephrectomy model (Nx) and the effect of an association between an AT-1 receptor blocker, losartan (L), and hydrochlorothiazide (H), shown previously to be effective when started one month after Nx. Adult male Munich-Wistar rats underwent Nx, being divided into four groups: Nx+V, no treatment;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 43 publications
9
43
0
Order By: Relevance
“…This notion is largely based on a few clinical observations performed over 50 years ago [26,27] . However, several recent clinical [28,29] and experimental [11][12][13] observations indicate that, in patients with advanced CKD, TTLDs are not only effective as antihypertensives but can even exert a renoprotective action, especially in combination with ACE inhibitors or AT-1 receptor blockers, an effect only partially shared with LDs. The present study suggests that protection against the development of HPT2 could be an additional reason for the preferential use of TTLDs in CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is largely based on a few clinical observations performed over 50 years ago [26,27] . However, several recent clinical [28,29] and experimental [11][12][13] observations indicate that, in patients with advanced CKD, TTLDs are not only effective as antihypertensives but can even exert a renoprotective action, especially in combination with ACE inhibitors or AT-1 receptor blockers, an effect only partially shared with LDs. The present study suggests that protection against the development of HPT2 could be an additional reason for the preferential use of TTLDs in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al [9] showed that TTLDs accelerate the differentiation of osteoblasts. Other TTLD effects unrelated to calcium excretion include vasodilation [1] , increase of plasma Klotho [10] and renoprotection in experimental CKD [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a variety of studies showed the presence of both Ang II and the receptor AT1 in the renal parenchyma of animals submitted to experimental models of CKD, leading to the discovery of a complex intrarenal pro-inflammatory RAAS that seems to become overactivated under kidney injury [18][19][20][21][22]. Accordingly, suppression of RAAS with both ACE inhibitors (ACEi) and/or AT1 receptor blockers (ARB) become a mainstay of treatment of progressive nephropathies and, although several innovative therapeutic measures have been recently proposed for the treatment of CKD, RAAS blockage, associated to diuretics or not, remains the best available resource in this regard [9,16,23,24].…”
Section: Overview Of Ckd Pathophysiologymentioning
confidence: 99%
“…Combining the ARB with nonhyperkalemic doses of spironolactone failed to further increase the regression of glomerulosclerosis [11]. Combining ARB with hydrochlorothiazide completely prevented progression of renal injury, even when it was initiated at advanced stages of the nephropathy (120 days after 5/6 nephrectomy) [34]. …”
Section: Rodent Models Of Progression Vs Regressionmentioning
confidence: 99%